Dynamic hydrologic modeling using the zero‐parameter Budyko model with instantaneous dryness index. Issue 18 (29th September 2016) - Biswal, Basudev
Abstract: Long‐term partitioning of hydrologic quantities is achieved by using the zero‐parameter Budyko model which defines a dryness index. However, this approach is not suitable for dynamic partitioning particularly at diminishing timescales, and therefore, a universally applicable zero‐parameter model remains elusive. Here an instantaneous dryness index is proposed which enables dynamic hydrologic modeling using the Budyko model. By introducing a "decay function" that characterizes the effects of antecedent rainfall and solar energy on the dryness state of a basin at a time, I propose the concept of instantaneous dryness index and use the Budyko function to perform continuous hydrologic partitioning. Using the same decay function, I then obtain discharge time series from the effective rainfall time series. The model is evaluated by considering data form 63 U.S. Geological Survey basins. Results indicate the possibility of using the proposed framework as an alternative platform for prediction in ungagued basins. Key Points: Dryness state of a basin is a dynamic or time‐varying phenomenon This study introduces a "decay function" that allows us to determine the dryness index of a basin at an instant of time The concept of dryness index helps in constructing a timescale‐independent zero‐parameter hydrological model